On the consequences of aluminium stress in rye: repression of two mitochondrial malate dehydrogenase mRNAs. (19th June 2014) - Abd El‐Moneim, D.; Contreras, R.; Silva‐Navas, J.; Gallego, F. J.; Figueiras, A. M.; Benito, C.; Whelan, J.
Abstract Plants have developed several external and internal aluminium (Al) tolerance mechanisms. The external mechanism best characterised is the exudation of organic acids induced by Al. Rye (Secale cereale L.), one of the most Al‐tolerant cereal crops, secretes both citrate and malate from its roots in response to Al. However, the role of malate dehydrogenase (MDH) genes in Al‐induced stress has not been studied in rye. We have isolated the ScMDH1 and ScMDH2 genes, encoding two different mitochondrial MDH isozymes, in three Al‐tolerant rye cultivars (Ailés, Imperial and Petkus) and one sensitive inbred rye line (Riodeva). These genes, which have seven exons and six introns, were located on the 1R (ScMDH1) and 3RL (ScMDH2) chromosomes. Exon 1 of ScMDH1 and exon 7 of ScMDH2 were the most variable among the different ryes. The hypothetical proteins encoded by these genes were classified as putative mitochondrial MDH isoforms. The phylogenetic relationships obtained using both cDNA and protein sequences indicated that the ScMDH1 and ScMDH2 proteins are orthologous to mitochondrial MDH1 and MDH2 proteins of different Poaceae species. The expression studies of the ScMDH1 and ScMDH2 genes indicate that it is more intense in roots than in leaves. Moreover, the amount of their corresponding mRNAs in roots from plants treated and not treated with Al was higher in the tolerant cultivar Petkus than in the sensitive inbred line Riodeva. In addition, ScMDH1 and ScMDH2 mRNA levels decreased in response to Al stress (repressive behaviour) in the roots of both the tolerant Petkus and the sensitive line Riodeva.